Exciton dissociation and charge trapping at poly(3-hexylthiophene)/phenyl-C61-butyric acid methyl ester bulk heterojunction interfaces: Photo-induced threshold voltage shifts in organic field-effect transistors and solar cells - Park, Byoungnam; You, Nam-Ho; Reichmanis, Elsa (AMER INST PHYSICS, 2012)
Photoinduced charge transfer at an electron donor/acceptor interface is one of the most crucial processes in determining the power conversion efficiency of organic solar cell devices. Here, we address exciton dissociation and charge carrier trapping at poly(3-hexylthiophene) (P3HT)/phenyl-C61-butyric acid methyl ester (PCBM) bulk heterojunction interfaces electrically using a field effect transistor (FET). With a P3HT/PCBM composite film, we elucidated exciton dissociation and charge carrier recombination assisted by localized electronic states at the P3HT/PCBM interface via photoinduced threshold voltage shift measurements with respect to wavelength using FETs in combination with organic solar cell devices. Interestingly, the combination of light coupled with a significant quantity of PCBM within the film was required to observe ambipolar charge transport in P3HT/PCBM FETs. This phenomenon was addressed by filling of electron traps associated with PCBM under illumination and formation of the conducting pathways for both electrons and holes. A high density of carrier traps at the interface suggested by the FET results was confirmed in light intensity dependent short-circuit current (J(sc)) and open-circuit voltage (V-oc) measurements using solar cell devices. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4705277]
Keywords: POLYMER; ILLUMINATION; FILMS